Līdzatkarīgo bērnu sociālo prasmju pilnveides iespējas Drabešu internātpamatskolā - Celmiņa, Liene (Latvijas Universitāte, 2007)
Nowadays a lot of children born and grow up in families where is alcoholic problems. It` s a heavy problem in Latvia, because alcoholic drinks can get very easy and one on parents are addictive from alcohol other begin to co-addictive and don` t take care about children. If it is for a long time, children have bad childhood and they social skill are not develop and it` s can cause the problems in school. Children cannot learn because they are worried about parents, they have shame about them and anger about that. And in school children it can see, because theses problems come out. Social skills are very important and necessary for every children and school must give a chance to develop them. If co-dependent children can develop their social skill author done the research in Drabešu boarding school. Author watch the children from class 1 to 4, in different situations- in different learning lessons, in free time, interesting circle. Author made a focus group interview with class 1 to 4 teacher about children social skills, interview with social pedagogue and three experts from Riga.
Development possibilities of social skills for codependent children in Drabesu school
Keywords: Sociālā politika un sociālā darba organizācija